(untitled) (International journal of artificial intelligence, 2024)
Inclusive education goes beyond physical accessibility. It recognizes that people have different learning styles, abilities, interests and cultural backgrounds. These changes, in turn, required changes in the activities of special teachers, transformation of their functional responsibilities and, accordingly, a revision of the list of necessary professionally significant and personal qualities. This article shows that by now the general and methodological issues of training special teachers to work with children with disabilities abroad have been studied quite well. By adapting teaching methods and curriculum to account for these differences, educators can ensure that every student can actively participate in the learning process.